Inside the Polish media firms: Accountability and transparency in the newsrooms - Głowacki, Michał (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
Although the majority of mechanisms and instruments which aim to support media ethics and journalistic professionalization in Poland were introduced at an early stage of political and social transformation in the 1990s, media accountability is still in the making. The moderate level of journalistic professionalization might be explained by the weakness of existing self regulatory mechanisms (codes of journalistic conduct, The Council of Media Ethics), divisions within journalistic communities (left wing-oriented vs. right-wing politically oriented) and the growing economic pressure. Bearing in mind that decision-making processes, supportive management as well as organizational structures and cultures might have an impact on journalistic behaviour and the understanding of roles and journalistic quality, this paper will go a long way in explaining the state of media accountability and transparency from the perspective of newsrooms. Referencing to the outcomes of empirical international research project “Media Accountability and Transparency in Europe (MediaAcT)” (2010–2013) the study will provide evidence similarities and differences in the perception of tools and existing practices by journalists from different types of media and job positions.